2012
DOI: 10.1109/tap.2011.2173102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hand on the Specific Absorption Rate in the Head

Abstract: The influence of the user's hand holding a mobile phone to the ear on the peak spatial-average Specific Absorption Rate (psSAR) averaged over any 1 g and 10 g of tissue in the head is investigated. This study is motivated by recent reports that found substantial increases in psSAR by the presence of the hand in some cases. Current measurement standards prescribe the measurement of SAR in a head phantom without a hand present. The mechanisms of interaction between the hand and mobile phone models are studied. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In Fig. 6, one specific hand grip was simulated, and the exact SAR values can change with different hand grips [12].…”
Section: B Average Simultaneous Sarmentioning
confidence: 99%
“…In Fig. 6, one specific hand grip was simulated, and the exact SAR values can change with different hand grips [12].…”
Section: B Average Simultaneous Sarmentioning
confidence: 99%
“…The results showed that the hand phantom brought slight impedance matching deterioration for both GSM frequency bands. Additionally, presence of the user's hand leads to less conservative SAR values to the human head [16]. The human hand leads to reduce the SAR values to the head tissues, as it dispels a part of antenna radiated energy [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…19 and IEC 60118-13, and an alternative tuned dipole near-field method also specified in ANSI C63. 19.…”
Section: Introductionmentioning
confidence: 99%